Isolation and Identification of Staphylococcus saprophyticus from Diseased Hybrid Sturgeon - Yeying Wu; Yalan Feng; Mingyang Xue; Zidong Xiao; Lijuan Jin; Ren Gao; Yahong Chen; Tianwang Liang; Yong Zhou (Fishes, 2023)
Hybrid sturgeon is an important economic fish species in China. In 2021, a bacterium was isolated from the liver and kidneys of freshwater-farmed hybrid sturgeon in Yichang City, Hubei Province, causing a disease with high mortality and surface bleeding. Through morphological observation, 16S rDNA gene sequence analysis, pathogenicity, an antimicrobial sensitivity test, as well as serum physiological and biochemical analysis, it was identified as Staphylococcus saprophyticus and named E702. The 16S rDNA gene sequence of E702 is highly homologous to S. saprophyticus in GenBank. Phylogenetic analysis showed that E702 and S. saprophyticus clustered into one clade. The 50% lethal dose of E702 was 2.14 × 105 CFU/g. The percentages of monocytes and eosinophils were markedly increased in the diseased sturgeon’s blood, whereas the percentages of platelets and lymphocytes were decreased. The activity levels of aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase in the diseased fish were significantly increased. The diseased fish suffered obvious damage to many tissues and organs, especially the liver and kidney, showing swelling, hyperemic and inflammatory cell infiltration. E702 was sensitive to antibiotics such as neomycin, cefazolin, norfloxacin, carbenicillin, gentamicin and ciprofloxacin. The study not only proved that S. saprophyticus was responsible for a great deal of hybrid sturgeon deaths, but also shed light on its potential risks in hybrid sturgeon farming. The research results provided the theoretical basis for the diagnosis as well as prevention of this disease.